POLITENESS STRATEGIES APPLIED BY TEACHERS IN EARLY CHILDHOOD EDUCATION - Ni Luh Sutrisna Diyani; I Nyoman Adi Jaya Putra; Ni Luh Putu Sri Adnyani (Undiksha Press, 2023)
Children tend to imitate adults such as teachers, not only in the way the teachers speak but also in the way the teachers think, behave, act, and solve problems. Politeness strategies that the teachers apply could be a way to motivate students to act and communicate politely. This study aims at analysing the positive and negative politeness strategies applied by teachers in early childhood education during the teaching and learning process, as well as analyzing the acts of teachers that threaten the students' negative faces and how the students respond to the teachers' face-threatening acts. The study involved three kindergarten teachers at an international school in Bali as the subjects. The data was collected during circle time activities. Circle time is when the teachers and children gather in a circle to discuss the day’s activities. The finding showed that the kindergarten teachers dominantly and consistently applied positive politeness strategies to motivate the students and build a close relationship between teachers and students during the teaching and learning process, which is 91.2%, compared with negative strategies, which were only 7.9%. Furthermore, there were 52 utterances of face-threatening acts done by kindergarten teachers in the dialogue interaction with their students. It is suggested that teachers consciously choose the appropriate politeness strategies, either positive or negative, to suit the context as well as the objectives of the instruction. Keywords: context, politeness strategy, face threatening acts, early childhood education, teacher